FOLKLORE IN LITERATURE LEARNING AS A MODEL FOR DEVELOPING CULTURAL CHARACTERS AND STUDENTS 'PERSONALITY - Anastasia Baan (Jurusan Sastra Indonesia, 2021)
Folklore is one of the literary genres which is a cultural product of society and belongs to the community. As a cultural product, folklore contains noble cultural values that are upheld and respected by the people. The messages conveyed in the folklore contain character education values that should be emulated by the reading community. Therefore, folklore can be a vehicle for learning and character building in students that can be conveyed through literary learning. Literature learning must be able to generate and foster good moral values in students that can make students behave in an acceptable manner by the community. Literature learning must be able to develop critical, creative, polite, responsible, disciplined, respectful attitudes to students, both in relation to themselves, relationships with others, and relationships with worship. These individual, social and religious values can be found in folklore. Therefore, learning literature should put more emphasis on the appreciation of folklore to foster local wisdom values in students.Key words: folklore, literature learning, cultural character, student personality